1999
DOI: 10.1590/s0102-05361999000300006
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação de esterco bovino e uréia na couve e seus reflexos nos teores de nitrato e na qualidade

Abstract: RESUMOO excesso de nitrato nos alimentos é indesejável devido à sua conversão a nitrito, composto conhecido por participar de reações formadoras de compostos cancerígenos e modificadores da hemoglobina. A influência da aplicação de esterco bovino, uréia e a associação destes nos teores de N-NO 3 -presente nos tecidos foliares de couve (Brassica oleracea var. acephala) foi avaliada, com o objetivo de verificar o efeito de fontes e doses diferentes de nitrogênio no acúmulo deste composto. Para tanto, um experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
1
4
0
2
Order By: Relevance
“…Research results show distinct responses to fertilizer sources on leafy vegetable yield. Zago et al (1999) evaluated the effect of urea, cattle manure and biofertilizer also found no significant differences between these sources in the collard yield, supporting the results presented here. Shingo and Ventura (2009) also verified that organic fertilization with different organic compounds and pyroligneous acid resulted in collard green yield similar to standard fertilization with mineral fertilizer.…”
Section: Collard Green Yieldsupporting
confidence: 89%
See 4 more Smart Citations
“…Research results show distinct responses to fertilizer sources on leafy vegetable yield. Zago et al (1999) evaluated the effect of urea, cattle manure and biofertilizer also found no significant differences between these sources in the collard yield, supporting the results presented here. Shingo and Ventura (2009) also verified that organic fertilization with different organic compounds and pyroligneous acid resulted in collard green yield similar to standard fertilization with mineral fertilizer.…”
Section: Collard Green Yieldsupporting
confidence: 89%
“…Still, in this table, leaf N concentration ranged from 29.0 to 35.7 g kg -1 and, was significantly greater with the application of mineral fertilizer (urea), and lower with the application of fertilizer organic (pig slurry or poultry manure. Zago et al (1999) also reported that the application of urea resulted in higher N concentration in the collard leaves when compared to the cattle manure addition. The higher N uptake with the mineral fertilizer application was due to the high solubility of the urea, resulting in an increase in the availability of this nutrient in the soil.…”
Section: Nitrogen Sources Number Of Leaves Per Plant Leaves Fresh Massmentioning
confidence: 93%
See 3 more Smart Citations